Dispatch Decision Making in an Air Medical Transport System. (September 2016) - Giang, Wayne C.W.; Hui, Lavinia; Donmez, Birsen; Ahghari, Mahvareh; MacDonald, Russell D.
Air medical transport relies on effective dispatching of air and land vehicles to provide the fastest and best care possible for patient transfers. These difficult dispatch decisions are characterized by high time pressure, uncertainty, and the dynamic and complex environment of medical transportation. This paper describes a preliminary study of the decision making processes that occur during dispatch decisions at Ornge, the air medical transportation system in Ontario, Canada. We drew upon the Critical Decision Method and the structured data analysis approach to understand the major decision points faced by Ornge's dispatchers, and the cues and sources of information attended to in those situations. We found that the decision points deal with three main goals: maintain situation awareness, match resource to transfer, and plan logistics of transfer. Furthermore, we found that time estimation might play an important role in helping dispatchers coordinate within the dispatch team and with their external partners. These findings may help improve the design of computer aided dispatch software to better support the goals of the dispatchers.